2004
DOI: 10.1126/science.1093857
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Genome Shotgun Sequencing of the Sargasso Sea

Abstract: We have applied "whole-genome shotgun sequencing" to microbial populations collected en masse on tangential flow and impact filters from seawater samples collected from the Sargasso Sea near Bermuda. A total of 1.045 billion base pairs of nonredundant sequence was generated, annotated, and analyzed to elucidate the gene content, diversity, and relative abundance of the organisms within these environmental samples. These data are estimated to derive from at least 1800 genomic species based on sequence relatedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

85
3,103
6
58

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,772 publications
(3,252 citation statements)
references
References 35 publications
85
3,103
6
58
Order By: Relevance
“…1 online), which ensures a high dosage of alkane hydroxylation genes. A search for alkB genes in sequenced marine organisms and the only marine metagenomic database available 19 revealed that only a comparatively small number of bacteria harbor alkB homologs and even fewer have multiple copies ( Supplementary Fig. 4 and Supplementary Table 1 online).…”
Section: Genomic Islands and Mobile Genetic Elementsmentioning
confidence: 99%
“…1 online), which ensures a high dosage of alkane hydroxylation genes. A search for alkB genes in sequenced marine organisms and the only marine metagenomic database available 19 revealed that only a comparatively small number of bacteria harbor alkB homologs and even fewer have multiple copies ( Supplementary Fig. 4 and Supplementary Table 1 online).…”
Section: Genomic Islands and Mobile Genetic Elementsmentioning
confidence: 99%
“…These examples represent the first steps towards engineering an entire biological system from the ground up. Massive sequencing efforts exploring the biodiversity of culturable organisms as well as metagenomes, such as the Sargasso Sea project [77], have generated a wealth of genetic information. These endeavors are providing novel biosynthetic pathway infor-mation that can be used to design optimized systems for every fuel category.…”
Section: Box 2 Microbial Sources Of Other Petrochemical Commoditiesmentioning
confidence: 99%
“…While eDNA has commonly been used to assess microbial diversity and abundance (Venter et al . 2004; Rusch et al . 2007), only recently has the technique been used to survey higher eukaryotes including fishes (Thomsen et al .…”
Section: Introductionmentioning
confidence: 99%